R-loops at microRNA encoding loci promote co-transcriptional processing of pri-miRNAs in plants - Gonzalo, Lucía (2022)
In most organisms, the maturation of nascent RNAs is coupled to transcription. Unlike in animals, the RNA polymerase II (RNAPII) transcribes microRNA genes (MIRNAs) as long and structurally variable pri-miRNAs in plants. Current evidence suggests that the miRNA biogenesis complex assembly initiates early during the transcription of pri-miRNAs in plants. However, it is unknown whether miRNA processing occurs co-transcriptionally. Here, we used native elongating transcript sequencing data and imaging techniques to demonstrate that plant miRNA biogenesis occurs coupled to transcription. We found that the entire biogenesis occurs co-transcriptionally for pri-miRNAs processed from the loop of the hairpin but requires a second nucleoplasmic step for those processed from the base. Furthermore, we found that co- and post-transcriptional miRNA processing mechanisms co-exist for most miRNAs in a dynamic balance. Notably, we discovered that R-loops, formed near the transcription start site region of MIRNAs, promote co-transcriptional pri-miRNA processing. Furthermore, our results suggest the neofunctionalization of co-transcriptionally processed miRNAs, boosting countless regulatory scenarios.